Relação entre polimorfismos nos genes VDR e MTHFR, marcadores inflamatórios e de estresse oxidativo e parâmetros clínicos com a ocorrência de retinopatia em diabetes mellitus tipo 2 - Nascimento, Rayner Anderson Ferreira do (2015)
Diabetic retinopathy (DR) is an important cause of acquired blindness among diabetics. Clinical factors are related to the risk for DR, in addition, genetic markers have been investigated, among them VDR and MTHFR polymorphisms, however, the impact of rs1801131 and rs1801133 polymorphisms is still inconclusive, while for rs1544410 there is a shortage in the literature. In this work the relationship of polymorphisms rs1544410, rs1801131 and rs1801133 with DR was investigated by cross-sectional study in a sample of 109 individuals with type 2 diabetes (T2DM) duration between 5 and 10 years. After ophthalmological screening a group of 40 affected and 69 unaffected by DR was composed. Genomic DNA was extracted from buccal cells. Genetic data were obtained by PCR-RFLP and analyzed using Fisher's exact test. Blood sample and urine for metabolic markers determinations were obtained in 62 subjects and the mean values were compared to the allele and genotype distribution of rs1544410. There was no association between alleles or genotypes of polymorphisms rs1801131 and rs1801133 with RD. The polymorphic allele b and genotypic group Bb + bb of rs1544410 were more frequent in the affected group with mild significance: [OR 0.5 (95% CI 0.31-0.98) p = 0.0478] and [OR 3.4 (95% CI 1.07-10.9) p = 0.496], respectively. None of the clinical variables were associated with rs1544410 although a trend towards higher values of C-reactive protein in patients allele b has been identified but not statistically significant. In conclusion, this study suggests that the sample investigated rs1544410 polymorphism of the VDR was related to the risk of DR, but not rs1801131 and rs1801133 MTHFR polymorphisms.